Impact of serum potassium on therapeutic prognosis of maintenance hemodialysis patients on angiotensin receptor antagonists. Issue 1 (December 2016) - Omae, Kiyotsugu; Ogawa, Tetsuya; Yoshikawa, Masao; Sakura, Hiroshi; Nitta, Kosaku
Abstract Background In chronic kidney disease patients, angiotensin receptor blockers (ARBs) have been known to increase serum potassium (K) levels. On the other hand, it has been reported that in patients on maintenance dialysis, both hyperkalemia and hypokalemia were related to poor prognosis. In this study, the prognosis with ARB treatment was investigated using a prospective cohort of dialysis patients that were divided into two groups according to pre-dialysis serum K levels: these were the low serum K group (below 4.6 mEq/L) and the high serum K group (4.6 mEq/L and higher). Methods A total of 260 patients in our dialysis database were classified into four groups according to their serum K level and ARB use. The survival curves of these groups were estimated by Kaplan–Meier method and compared using a log-rank test. Using Cox regression model, prognostic factors for all-cause mortality were extracted from background factors, including the three classifications; high serum K and ARB group that served as the control. Results In terms of all-cause mortality rates, the low serum K and ARB group had the highest, whereas the high serum K and ARB group had the lowest. In the Cox regression model, all three classifications, except the control group, were factors for poor prognosis. Conclusions In this study, pre-dialysis serum K level and ARB use affected all-cause mortality of dialysis patients. Multi-center prospective randomized study will be needed in the future to validate our findings.